2011
DOI: 10.1002/hep.24575
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: An innate antiviral agent suppressing hepatitis C virus in human hepatocytes

Abstract: Vitamin D supplementation was reported to improve the probability of achieving a sustained virological response when combined with antiviral treatment against hepatitis C virus (HCV). Our aim was to determine the in vitro potential of vitamin D to inhibit HCV infectious virus production and explore the mechanism(s) of inhibition. Here we show that vitamin D 3 remarkably inhibits HCV production in Huh7.5 hepatoma cells. These cells express CYP27B1, the gene encoding for the enzyme responsible for the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 41 publications
(67 reference statements)
7
149
1
5
Order By: Relevance
“…A similar mode of action has been reported for antibacterial effects of vitamin D in monocytes 11,12 and antiviral responses to vitamin D in human hepatocytes. 17 Intracrine responses to vitamin D appear to be exquisitely sensitive to the availability of substrate 25D, 11,12,18 suggesting that the hepcidin-ferroportin homeostasis system may be influenced by serum vitamin D (25D) status ( Figure 5). This hypothesis is supported by supplementation data from healthy volunteers showing that elevated serum concentrations of 25D (but not 1,25D) after a single oral dose of vitamin D 2 produced a 34% decrease in serum hepcidin concentrations that persisted for 72 hours (Figure 4).…”
Section: Effect Of Vitamin D Supplementation On Circulating Hepcidin mentioning
confidence: 99%
“…A similar mode of action has been reported for antibacterial effects of vitamin D in monocytes 11,12 and antiviral responses to vitamin D in human hepatocytes. 17 Intracrine responses to vitamin D appear to be exquisitely sensitive to the availability of substrate 25D, 11,12,18 suggesting that the hepcidin-ferroportin homeostasis system may be influenced by serum vitamin D (25D) status ( Figure 5). This hypothesis is supported by supplementation data from healthy volunteers showing that elevated serum concentrations of 25D (but not 1,25D) after a single oral dose of vitamin D 2 produced a 34% decrease in serum hepcidin concentrations that persisted for 72 hours (Figure 4).…”
Section: Effect Of Vitamin D Supplementation On Circulating Hepcidin mentioning
confidence: 99%
“…Az irodalomból ismert, hogy hepatitis C-vírus-fertőzés esetén a májszövetben megemelkedik a helyi 1,25-dihidroxi-D 3 -vitamin-aktivitás az inaktiváló CYP24A1-expresszió csökkenésének hatására [56]. Egyik hepatitis C-vírus-fertőzött betegünk hepatocellularis carcinomájában sem volt kimutatható a CYP24A1 expressziója.…”
Section: Táblázatunclassified
“…Vitamin D anti-inflammatory and modulating properties could impact on disease progression especially on HCV chronic liver disease (12) . Some authors observed that vitamin D might have an impact on other outcomes and in the response to the treatment of patients with chronic hepatitis C (8,18,21,26) .…”
Section: Discussionmentioning
confidence: 99%